2016
DOI: 10.1096/fj.201600240rr
|View full text |Cite
|
Sign up to set email alerts
|

Tetraspanin‐2 promotes glucotoxic apoptosis by regulating the JNK/β‐catenin signaling pathway in human pancreatic β cells

Abstract: Diabetes mellitus is a complex and heterogeneous disease, which has β-cell dysfunction at its core. Glucotoxicity affects pancreatic islets, causing β-cell apoptosis. However, the role of JNK/β-catenin signaling in glucotoxic β-cell apoptosis is not well understood. Recently, we identified tetraspanin-2 (TSPAN2) protein as a proapoptotic β-cell factor induced by glucose, suggesting that TSPAN2 might contribute to pancreatic β-cell glucotoxicity. To investigate the effects of glucose concentration on TSPAN2 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…At high glucose concentrations, Tspan2 appeared to induce apoptosis of a human pancreatic β-cell line by modulating the JNK/β-catenin signalling pathway, suggesting a potential therapeutic approach against the glucotoxic apoptosis in diabetes [95]. The TSPAN2 gene locus has also recently been identified as a risk factor for ischaemic stroke [96].…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…At high glucose concentrations, Tspan2 appeared to induce apoptosis of a human pancreatic β-cell line by modulating the JNK/β-catenin signalling pathway, suggesting a potential therapeutic approach against the glucotoxic apoptosis in diabetes [95]. The TSPAN2 gene locus has also recently been identified as a risk factor for ischaemic stroke [96].…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…TSPAN2 is a newly identified TSPAN family member that suppresses inflammation in the CNS (22), regulates cell motility in lung cancer (23), and promotes glucotoxic apoptosis in human pancreatic β cells (24). More recently, a genome‐wide association study (GWAS) identified a single‐nucleotide polymorphism (SNP) that is located in the regulatory region of TSPAN2 and is strongly associated with atherosclerosis in large arteries (25).…”
mentioning
confidence: 99%
“…No matter what, we demonstrated that Sophoridine-induced β-catenin degradation was not depended on ubiquitin-proteasome pathway but depended on ESRRG, which enhances β-catenin degradation in an ubiquitin-proteasome independent manner [21] . Since ESRRG is a downstream signaling protein of MAPK pathways and the activation of MAPKs ERK1/2, p38 and JNK1/2 promote the phosphorylation of β-catenin [32][33][34] , Sophoridine may enhance β-catenin degradation via an MAPK/ESRRG pathway.…”
Section: Discussionmentioning
confidence: 99%